ANALISIS SENSITIVITAS RESIKO INVESTASI PROYEK INFRASTRUKTUR JALAN TOL - Fitriani, Heni (CANTILEVER, 2007)
Investment evaluation on infastruchre requires careful analysis and should consider risks and uncertainties due to its unpredictable outcomes. Risk derives from our inability to see into the future, and indicates a degree of uncertainty. This paper presents the alternative approach- Sensitivity Analysis- in evaluating the most critical variables of risks which influence the investment decision on toll roads. @RISK makes it easier to see the impact of uncertain model parameters on the results and offers a powerful analysis technique for selecting between available alternatives. An advanced sensitivity analysis using Tornado Graph or Spider Graph will give the same information on the changing of the outputs.